Impacts of Interventions during Early Childhood on Later Outcomes : A Systematic Review - Independent Evaluation Group (World Bank, Washington, DC, 2015)
In an effort to bridge the evidence gap, the Independent Evaluation Group (IEG) prepared a systematic review that gathers and analyzes the available impact evaluation evidence in developing countries from 1990 to 2013 on whether early childhood interventions shape future outcomes. Its purpose is not to supplant existing evidence but rather to help practitioners understand how evidence from impact evaluations supports or challenges beliefs about interventions and can be used to inform development policy. This review aims to answer two questions: (1) What is the evidence of attributable effects on outcomes in primary school and beyond from interventions in low- and middle-income countries that occur during the early childhood period? and (2) How do the post-early childhood effects of early childhood interventions vary by socioeconomic status, gender, age at intervention, and age at evaluation, particularly during the first 1,000 days from conception to the childs second birthday and from age three to primary school enrollment at age five to six? This report reviews all interventions from developing countries that occur during early childhood for which impact evaluation estimates exist for effects observed at primary school age and older. From an initial search of thousands of studies, the search process which included database searches, hand searches, and snowballing identified more than 500 relevant impact evaluations written from 1990 to 2015. This review covers six areas or domains of human development: physical development, cognitive development, language development, socio-emotional development, schooling outcomes, and employment and labor market outcomes. These domains are commonly included in evaluations of early interventions targeting poor children because they are negatively affected by early poverty, can benefit from early intervention, and are important for overall well-being or adult productivity. Some outcomes can be measured repeatedly starting from early childhood (i.e., height and weight) while others are only measurable later in life (i.e., cognition, schooling, and employment and labor market status).